Interfacial reactions between solid Ni and liquid Sn-Zn alloys - Gandova V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The limitation of the harmful lead-containing solders used in the electronics and other industry applications change lead with another metals. Interfacial reactions between Sn-Zn alloys and Ni substrate after annealing at 400 and 450°C were studied. Three intermetallic compounds Ni3Sn4, T1, γ-Ni5Zn21 and liquid Sn were observed in the Ni/Sn-Zn diffusion couples. Scanning electron microscope was used for the investigation of the microstructure. The microhardness measurement of the intermetallic layers was also performed.